2020
DOI: 10.3390/diagnostics10090656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H19 Polymorphisms on Prostate Cancer Clinicopathologic Characteristics

Abstract: Active surveillance is the preferred strategy for very low risk, low risk, and some favorable intermediate risk of prostate cancer. However, the current risk stratifications with initial prostate-specific antigen (iPSA) levels and Gleason scores at biopsy can underestimate the true oncologic threat. More precise predictors are required to avoid the overtreatment of prostate cancer. H19 single-nucleotide polymorphisms (SNPs) have been found to play crucial roles in numerous malignancies, but not yet in prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Five SNPs of LncRNA H19, including the rs217727 (C/T), the rs2107425 (C/T), the rs2839698 (C/T), the rs3024270 (C/G), and the rs3741219 (A/G) were selected due to the related studies conducted earlier [ 21 , 22 ]. About the genotyping steps which use the same method as previous research [ 17 ], the DNA was firstly extracted from the leukocytes of the venous blood from each patient via the usage of the QIAamp DNA kits (Qiagen, Valencia, CA, USA) according to manufacturer’s guide instruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five SNPs of LncRNA H19, including the rs217727 (C/T), the rs2107425 (C/T), the rs2839698 (C/T), the rs3024270 (C/G), and the rs3741219 (A/G) were selected due to the related studies conducted earlier [ 21 , 22 ]. About the genotyping steps which use the same method as previous research [ 17 ], the DNA was firstly extracted from the leukocytes of the venous blood from each patient via the usage of the QIAamp DNA kits (Qiagen, Valencia, CA, USA) according to manufacturer’s guide instruction.…”
Section: Methodsmentioning
confidence: 99%
“…The Long Noncoding RNA (LncRNA) refers to a family of genetic sequences that do not contribute to the synthesis of protein but can regulate certain cellular functions like chromatin remodeling, cell cycle advancement, and neoplasm formation [ 18 , 19 ]. Among the LncRNA, the LncRNA H19 revealed certain associations to several types of cancers [ 20 , 21 , 22 ]. For the field of lung cancers, the high level of LncRNA H19 expression would lead to gefitinib resistance in non-small cell lung cancer, [ 23 ] and the presence of LncRNA H19 are associated with the proliferation of lung cancer cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The medical information including the age at diagnosis (years), initial PSA level at diagnosis (ng/ml), clinical and pathological TNM staging, pathologic Gleason grade group, perineural invasion, seminal vesicle invasion, lymphovascular invasion, biochemical recurrence and D'Amico classification was acquired from the personal medical records for each patient. 38 Before this study started to initiate, the certification and approval was confirmed by the Institutional Review Broad (IRB) of the Taichung Veteran General Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is an extension of our previous work exploring the predisposition of risk SNPs in prostate cancer and differentiating patients with extremely low oncologic risk from those traditionally defined as low risk in the D’Amico classification [ 25 , 26 , 27 ]. Thus, we divided the patients into three groups on the basis of their iPSA at diagnosis (iPSA ≤ 7 ng/mL, iPSA 7–10 ng/mL, and iPSA > 10 ng/mL) to analyze the role of MALAT1 genotyping variation as a function of different levels of malignant potential in prostate cancer.…”
Section: Methodsmentioning
confidence: 99%